درجة إستعاب وفهم أساتذة مادة اللغة العربية للمفاهيم والمصطلحات الواردة في الكتاب المدرسي وفق منهاج الجيل الثاني للسنة الأولى متوسط. دراسة استكشافية بمتوسطات الأغواط - لشلق فاطمة الزهرة; شويرب لمياء; ملياني عبد الكريم (My University, 2017)
The present study aimed to know the degree of comprehension and understanding of Arabic language teachers of concepts and teaching terms. The textbook of the second generation curriculum, where the new reforms play an effective role in the need to understand the information by the teachers before the delivery of the student where he does not have difficulty in understanding the concepts and new formulas that the experienced professors do not have difficulty in understanding and find several ways to communicate concepts as it is because experience Teacher Learning Multiple Ways and Perception of Every Student Through this study we will explore the degree to which teachers change teaching methods to communicate information easily and in a simplified way to understand new concepts and terms. These objectives were used descriptive analytical method. Which is appropriate in our view of the nature of the study. The questionnaire was used as a data collection tool. This study is determined by a sample of 60 professors of Arabic language, distributed over 13 intermediate schools in the state of Laghouat. With 38 professors and 22 professors. This study was conducted during the academic year 2016-2017. The results of this study were as follows: 1- Medium degree of the absorption of Arabic language teachers in the intermediate stage of the second generation curriculum for the first year of average. 2- There are no statistically significant differences between Arabic language teachers in the degree of comprehension of the secondgeneration curriculum for the first year of average attributed to the variable sex?. 3- The absence of statistically significant differences between the Arabic language teachers in the degree of assimilation of the second generation curriculum for the first year of the average attributed to the variable professional experience? The Second Generation Curriculum, Professor, Arabic Language, Intermediate Education.